Who sends money home: Fiscal consequences of the territorial representation in Serbia - Vučićević Dušan; Bursać Dejan (Srpska Politička Misao)
The practice of political representatives trying to provide benefits to voters in their local communities is not new. The phenomenon is most often operationalized through financing of public works, projects, subsidies, direct transfers or social benefits, provided in order to increase the political ratings and ultimately ensure reelection. Although the practice is more pronounced in candidate-oriented electoral systems consisting of single-member districts, it can also be identified within the countries employing the proportional list system. The authors' intention is to examine a correlation between the local representation in the Serbian parliament and budgetary transfers and moreover a general level of local financing. For this purpose, data on the residence of MPs was compared with the levels of transfers, subsidies and amount of local expenditures, while the models are additionally controlled with various variables including size of municipality, development level, unemployment rate, share of elderly population, as well as other developmental and societal factors. The sample covered 145 cities and municipalities in Serbia, for a period from 2013 to 2021. The empirical results indicate that pork barrel practices are indeed present even in the environment of closed electoral lists with at-large single district, which does not create institutional incentives for the cultivation of personal vote. But even in Serbia, it seems that local politicians favor their places of residence by increasing the level of public investments. Consequently, municipalities without deputies will remain without financial benefits that parliamentary representation provides. We found that these practices are primarily accomplished through central level subsidies, but can also be identified in the amounts of local budgets and local expenditures. On the other hand, direct annual transfers from the higher levels of government are mostly fixed due to the exact legal criteria, exempting the interference of elected deputies on this particular financing mechanism.